A field guide to the ferns and their related families of Northeastern and Central North America with a section on species also found in the British Isles and Western Europe - Cobb, Boughton (Boston Houghton Mifflin Company, 1984)
A handbook of ferns and their related families in the North American continent based on visual identification.
Includes bibliographical references (pages [263]-267) and index.
Keywords: Ferns -- North America